Liver cancer: contributory factors, diagnosis and treatment - Murtaza Mustafa; EM Illzam; RK Muniandy; AM Sharifa; K Fairrul; MK Nang; J Sidra (International Organization of Scientific Research (IOSR), 2016)
Liver cancer have high mortality secondary to hepatitis B,hepatitis C and secondary to alcohol.Hepatocellular carcinoma (HCC),most common form of liver cancer with highest rates in China and in Sub-Saharan Africa. Approximately 75% of all primary liver cancer is HCC (also named hepatoma). Cholangiocarcinoma can form within liver as the bile duct.Liver fluke infection increases the risk of cholangiocarcinoma in Thailand.Tumor of blood vessels-angiosarcoma.Cancers produced from muscles in the liver are leiomyosarcoma.Many cancers in the liver are due to metastasis. Contributory factors of liver cancer includes: viral infection either with hepatitis C (HCV) or hepatitis B (HBV). Viruses cause HCC because massive inflammation, fibrosis and eventual cirrhosis within the liver. Aflatoxin exposure can lead to the development of HCC. High grade dysplastic nodules are precancerous lesions of the liver. Beckwith-Weidemann syndrome is associated with hepatoblastoma in children. Liver cancer is associated with abdominal mass, abdominal pain, emesis, anemia, back pain, jaundice, itching, weight loss and fever. Diagnosis mainly by ultrasound, CT, MRI, and magnetic resonance cholangiopancreatography (MRCP). Tests for tumor markers are helpful. Treatment by surgery, antiviral drugs and liver transplant. Prevention by reducing exposure to risk factor for liver cancer, vaccination against hepatitis B virus, reducing alcohol abuse,prevention of carcinogenesis and treatment to prevent recurrence of liver cancer, by the chemotherapy drugs and antiviral drugs.With the advances in diagnosis and treatment the prognosis in liver cancer remains poor.